2021
DOI: 10.1212/wnl.0000000000011701
|View full text |Cite
|
Sign up to set email alerts
|

Financial Conflicts of Interest of United States–Based Authors in Neurology Journals

Abstract: ObjectiveTo detail the scope, nature, and disclosure of financial conflicts of interest (COI) between the pharmaceutical and medical device industries (Industry) and authors in high-impact clinical neurology journals.MethodsUsing the Centers for Medicare and Medicaid Services Open Payments database (OPD), we retrieved information on payments from Industry to 2,000 authors from randomly selected 2016 articles in 5 journals. We categorized payments by type (Research, General, and Associated Research/institutiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“… 50 While some studies have documented an association between general payments, 51 including consultancies, 52 and positive clinical trial outcomes, others have established no such relationship. 53 Further, undisclosed general payments, detected by comparing Open Payments with researchers’ self-reporting, are widespread in articles presenting findings from research studies, 54 - 56 including reports of clinical trials. 57 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 50 While some studies have documented an association between general payments, 51 including consultancies, 52 and positive clinical trial outcomes, others have established no such relationship. 53 Further, undisclosed general payments, detected by comparing Open Payments with researchers’ self-reporting, are widespread in articles presenting findings from research studies, 54 - 56 including reports of clinical trials. 57 …”
Section: Introductionmentioning
confidence: 99%
“…In addition to research payments made to individual physicians, Open Payments covers payments for “associated research,” including grants, 57 made to “a research institution or entity where a physician is named as a principal investigator on the research project.” 74 Payments for associated research have attracted even less scrutiny than research payments, consistent with the exclusion of research institutions, such as universities, from the US Sunshine Act disclosure requirements. 48 Nevertheless, in some specialties, such as neurology 54 or oncology, 57 the value of organisational-level payments for associated research has exceeded individual-level research payments. In these specialties, undisclosed payments for associated research were also worth more than undisclosed research payments.…”
Section: Introductionmentioning
confidence: 99%
“…The adverse effects of the large disclosure gap between mandatory and voluntary payments in the USA were documented by comparing OPD payments for 200 OPD-listed physician authors of articles published in high-impact clinical neurology journals with authors’ self-disclosed journal payments 18. Of 2239 general payments from 2013 to 2016 to these authors, from companies making products directly tested or discussed in their article, 970 (43%) were not disclosed by authors.…”
Section: Can Full Public Disclosure Be Accomplished?mentioning
confidence: 99%
“…The average general payment per author was $114 722, with the maximum of $876 952 for a single author. The study’s authors concluded that ‘Industry-related financial relationships are prevalent among United States–based physicians publishing in major neurology journals, and incomplete self-disclosure is common……academic and other neurologists must work to establish firm rules to ensure and manage disclosure of financial COI’ 18…”
Section: Can Full Public Disclosure Be Accomplished?mentioning
confidence: 99%
“…Therefore, they should be keen to present all conflicting or controversial viewpoints on the research question in a scientifically impartial manner. [19,36] Note that initially captured references may need to be updated by the time one starts writing the discussion section. The unwary inclusion of references from predatory journals to support statements made in the discussion can be counterproductive in many ways.…”
Section: Citing the Literaturementioning
confidence: 99%